Analisis Efisiensi Berbagai Saluran Pemasaran Beras Produksi Lokal Di Kabupaten Tanjung Jabung Timur - Elwadinata, Frenco (Brida Provinsi Jambi, 2025)
Marketing is a process of distributing products from producers to consumers, accompanied by an increase in utility value through processing, transportation, and storage. The number of entities involved in the marketing channel influences the total cost, making selecting the appropriate channel a critical factor in ensuring cost efficiency. This study aims to describe the marketing channels, marketing entities, and marketing functions of rice, as well as to analyze the efficiency of rice marketing in Tanjung Jabung Timur Regency. A descriptive qualitative method was used to analyze the channels, entities, and functions, while a descriptive quantitative method was employed to evaluate marketing efficiency through margin analysis, farmer's share, and the cost-to-benefit ratio. The study identified four main entities in rice marketing: farmers, rice mills/village-level collectors, district-level collectors, and retailers, organized into five marketing channel patterns. All channels were efficient, with Channels 1 and 2 being the most efficient due to direct sales from farmers to consumers.